Gas-Liquid Two-Phase Flow in Up and Down Vertical Pipes - Almabrok, Almabrok Abushanaf (Cranfield University, 2013)
Multiphase flows occurring in pipelines with a serpentine configuration is an important phenomenon, which can be encountered in heat exchangers used in a variety of industrial processes. More specifically, in many industrial units such as a large cracking furnace in a refinery, the tubes are arranged in a serpentine manner and are relatively short. As flow negotiates round the 180o bend at the ends of the tubes, the generated centrifugal force could cause flow maldistribution creating local dry spots, where no steady liquid film is formed on the adjacent straight sections of the pipe. As a result, events including coking, cracking and overheating of heat transfer surfaces may occur and lead to frequent shutdown of the facilities. Consequently, this could increase operating costs and reduce production revenue. Thus, it is desirable to know the effect that the bends exert on the flow in the straight part of the pipe. Apart from this, knowledge of the bend effects on the flows in the pipeline could also be important for the design of other pipelines for gas/liquid transport, e.g. offshore gas and oil pipelines. Quite a large number of studies have been found in the literature. The majority of them were for two-phase flow with small diameter pipes (i.d. ≤ 50 mm). However, studies with large diameter pipes (i.d. ≥ 100 mm), have increasingly been considered in recent years as problems related to large diameter vertical pipes are being encountered more and more often in industrial situations. This thesis studies the effect of 180o bends on the characteristics and development of gas-liquid two-phase flows in large diameter downward and upward pipes. The study particularly focuses on the influence of serpentine configuration on flow structure, cross-sectional void distribution and circumferential liquid film profiles and their development along the downward and upward sections. It was found that both the top and bottom bends have considerable impacts on flow behaviour, although to varying degrees. These impacts were highly dependent on the air and water flow rates. For sufficient flow rates, the bends were observed to create flow maldistribution in the adjacent straight section, due to the effects of centrifugal force. The air moved towards the inner zone of the bend and the water towards the outer zone, while a lesser quantity of water was identified on the other surfaces of the pipe. Investigation of the film thickness development in the downward and upward sections showed that, the liquid film behaviour close to the bends was significantly different from those located further away. This can be attributed to the centrifugal force of the bends. Examination of the power spectral density (PSD) along the downward and upward sections showed that, the shape of PSD located in the adjacent section to the bends, was substantially different from those located further away. Furthermore, several flow regime maps were generated which showed that, in addition to bubbly, intermittent and annular flows, unstable flows existed along the upward section, particularly for low gas and water flow rates. In this study it was found that, the lower bend was periodically blocked by the liquid and then blown through by the accumulated air. The data obtained from this study were compared with different theoretical correlations found in the existing literature. Some discrepancy between the results of the current study and those of previous published materials was noted. Updated correlations were presented which provided well results when they applied for the data obtained from the current study and previous studies.
Keywords: Serpentine configuration; downward; upward; bends; liquid film thickness; void fraction distribution; PSD; flow regime maps